Effectiveness of Edible Coating Aloe Vera on the Quality of Papaya Fruit (Carica papaya L) During Storage - Bardevi, Fathia; Taib, Eva Nauli; Amin, Nurdin; Zuraidah, Zuraidah; Rahmawati, Lina (Jurnal Biologi Tropis, 2026)
Papaya (Carica papaya L.) is a highly perishable climacteric fruit with limited shelf life at room temperature due to rapid respiration and transpiration. This study aimed to evaluate the effect of different concentrations of Aloe vera gel edible coating on weight loss, color change, and fruit firmness of California variety papaya during room temperature storage. A Completely Randomized Design (CRD) with four treatment levels was applied: K0 = 0% (control), K1 = 60%, K2 = 80%, and K3 = 100% Aloe vera gel concentration, each replicated four times. Papaya fruits were coated by immersion for 5 minutes and stored at room temperature (±25–28°C) for 8 days. Parameters measured included weight loss (%), fruit color (L*, a*, b* values using a colorimeter), and fruit firmness (Newton, using a penetrometer). Data were analyzed using one-way ANOVA at a 5% significance level, followed by Duncan's Multiple Range Test (DMRT). Results showed that Aloe vera gel edible coating significantly affected all quality parameters during storage. Treatment K2 (80% concentration) consistently demonstrated the best performance, exhibiting the lowest weight loss (1.0775%), most effective inhibition of color changes (highest b* value of 56.400 on day 6; lowest a* value of 2.450 on day 8), and highest fruit firmness (2.800 ± 0.356 N) compared to other treatments. The semi-permeable layer formed at this optimal concentration effectively reduced transpiration and respiration rates without triggering anaerobic fermentation. It is concluded that Aloe vera gel edible coating at 80% concentration is the most effective treatment for maintaining papaya fruit quality during room temperature storage.